Extracellular SPARC cooperates with TGF-β signalling to induce pro-fibrotic activation of systemic sclerosis patient dermal fibroblasts. (16th December 2019) - Carvalheiro, Tiago; Malvar Fernández, Beatriz; Ottria, Andrea; Giovannone, Barbara; Marut, Wioleta; Reedquist, Kris A; Garcia, Samuel; Radstake, Timothy R
Abstract: Objectives: SSc is an autoimmune disease characterized by inflammation, vascular injury and excessive fibrosis in multiple organs. Secreted protein acidic and rich in cysteine (SPARC) is a matricellular glycoprotein that regulates processes involved in SSc pathology, such as inflammation and fibrosis. In vivo and in vitro studies have implicated SPARC in SSc, but it is unclear if the pro-fibrotic effects of SPARC on fibroblasts are a result of intracellular signalling or fibroblast interactions with extracellular SPARC hampering further development of SPARC as a potential therapeutic target. This study aimed to analyse the potential role of exogenous SPARC as a regulator of fibrosis in SSc. Methods: Dermal fibroblasts from both healthy controls and SSc patients were stimulated with SPARC alone or in combination with TGF-β1, in the absence or presence of a TGF receptor 1 inhibitor. mRNA and protein expression of extracellular matrix components and other fibrosis-related mediators were measured by quantitative PCR and western blot. Results: Exogenous SPARC induced mRNA and protein expression of collagen I, collagen IV, fibronectin 1, TGF-β and SPARC by dermal fibroblasts from SSc patients, but not from healthy controls. Importantly, exogenous SPARC induced the activation of the tyrosine kinase SMAD2 and pro-fibrotic gene expression induced by SPARC in SSc fibroblasts was abrogated by inhibition of TGF-β signalling. Conclusion: These results indicate that exogenous SPARC is an important pro-fibrotic mediator contributing to the pathology driving SSc but in a TGF-β dependent manner. Therefore, SPARC could be a promising therapeutic target for reducing fibrosis in SSc patients, even in late states of the disease.